2011
DOI: 10.1246/bcsj.20110080
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aggregation State and Electrical Properties of Terthiophenes/Imogolite Nanohybrids

Abstract: Organic/inorganic nanohybrid materials composed of terthiophenes and imogolite were prepared by means of specific surface interaction between a phosphonic acid group in terthiophene derivatives and aluminol groups on the surface of imogolite. The new materials were investigated by FTIR, UVvis absorption, fluorescence spectroscopy, TEM observation, nitrogen adsorptiondesorption, and IV measurement. Addition of terthiophene of phosphonic acid derivatives into imogolite brought some changes in absorption and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…An efficient way to modify a metal oxide surface is to use phosphonate derivatives [126]. This issue has been extensively studied [127][128][129][130][131][132][133][134][135][136] since 2001 and the first report of the chemisorption of octadecylphosphonic acid onto the outer surface of imogolite nanotubes [127]. Successful grafting of organic moieties can be evidenced by dispersing unmodified and modified nanotubes in organic solvents ( Figure 5.8) [131,135,137].…”
Section: Surface Functionalization Of Imogolite Nanotubesmentioning
confidence: 99%
“…An efficient way to modify a metal oxide surface is to use phosphonate derivatives [126]. This issue has been extensively studied [127][128][129][130][131][132][133][134][135][136] since 2001 and the first report of the chemisorption of octadecylphosphonic acid onto the outer surface of imogolite nanotubes [127]. Successful grafting of organic moieties can be evidenced by dispersing unmodified and modified nanotubes in organic solvents ( Figure 5.8) [131,135,137].…”
Section: Surface Functionalization Of Imogolite Nanotubesmentioning
confidence: 99%
“…The obtained results challenge the commonly used scheme of grafted imogolite, where the phosphonic acid reacts with OH groups on the external wall of imogolite and forms covalent bonds by condensation. [18][19][21][22] IR, 31 The basis for this reactivity is the surface chemistry of imogolite, which is similar to gibbsite. The tube wall is covered in bridging Al 2 (µ-OH) groups that correspond to the crystal face of gibbsite, while the terminal points have Al-OH / Al-OH 2 + groups, similar to the crystal edges of gibbsite.…”
Section: Degradation Versus Surface Modificationmentioning
confidence: 99%
“…However, most of the studies aim to graft octadecylphosphonic acid or other phosphonic acids onto imogolite. [14][15][16][17][18][19][20][21][22] Yamamoto et al were the first to study the chemisorption of octadecylphosphonic acid (ODPA) on imogolite. [14][15] They concluded that ODPA adsorbs to the surface of imogolite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations